Journal of Economic Perspectives - American Economic Association (Pittsburgh, PA American Economic Association, 1996)
The Journal of Economic Perspectives (JEP) attempts to fill a gap between the general interest press and most other academic economics journals. The journal aims to publish articles that will serve several goals: to synthesize and integrate lessons learned from active lines of economic research; to provide economic analysis of public policy issues; to encourage cross-fertilization of ideas among the fields of thinking; to offer readers an accessible source for state-of-the-art economic thinking; to suggest directions for future research; to provide insights and readings for classroom use; and to address issues relating to the economics profession. Articles appearing in the journal are normally solicited by the editors and associate editors. Proposals for topics and authors should be directed to the journal office
JEP is published quarterly February (winter), May (Spring), August (Summer) and November (Fall)
Keywords: Economics; ECONOMIC POLICY; ECONOMIC RESEARCH; ECONOMIC ANALYSIS; PERIODICALS